Safety Assessment of Apple-Derived Ingredients as Used in Cosmetics. (June 2023) - Johnson, Wilbur; Bergfeld, Wilma F.; Belsito, Donald V.; Hill, Ronald A.; Klaassen, Curtis D.; Liebler, Daniel C.; Marks, James G.; Shank, Ronald C.; Slaga, Thomas J.; Snyder, Paul W.; Gill, Lillian J.; Heldreth, Bart
The Expert Panel for Cosmetic Ingredient Safety (Panel) reviewed the safety of 26 apple-derived ingredients, which reportedly function mostly as skin conditioning agents in cosmetic products. Because apple-derived ingredients may be obtained from different apple cultivars, the composition of ingredients derived from different cultivars should be similar to that of ingredients reviewed in this safety assessment. Additionally, industry should continue to use good manufacturing practices to limit impurities that could be present in botanical ingredients. The Panel reviewed the available data to determine the safety of these ingredients and concluded that 21 of these ingredients are safe in cosmetics in the present practices of use and concentrations described in this safety assessment. However, the Panel also determined that the available data are insufficient to determine the safety of Pyrus Malus (Apple) Root Extract, Pyrus Malus (or Malus Domestica) (Apple) Stem Extract, Malus Domestica (Apple) Callus Extract, and Malus Domestica (Apple) Oil.